Optimal motivation in Peruvian high schools: Should learners pursue and teachers promote mastery goals, performance-approach goals or both? - Matos, L.; Lens, W.; Vansteenkiste, M.; Mouratidis, A. (Learning and Individual Differences, 2017)
Achievement goal theory is an important framework to understand students' achievement goals, motivation, and engagement in academic situations and to study teachers' instructional practices. There has been a debate about whether optimal motivation involves the pursuit of mastery goals only (i.e., mastery goal perspective) or the combined pursuit of mastery and performance-approach goals (i.e., multiple goal perspective; Barron & Harackiewicz, 2001, 2003). In the present correlational research we tested these two goal perspectives in two Peruvian samples of high school students (Sample 1: N = 1505; Sample 2: N = 551) and further examined whether students in classes, in which teachers were perceived to promote mastery goals only or performance-approach goals, would display the most optimal learning pattern. After controlling for learners' performance-avoidance goal pursuit, results provided only slim evidence for the additive goal perspective, as the effects of students' pursuit of mastery goals were more robust and consistent across both samples and outcomes (i.e., learning strategies and math grades). Along similar lines, at the class level, perceived teacher-promoted mastery goals positively predicted deep-level learning strategies, while class-level perceived teacher-promoted performance-avoidance goals related to lower academic achievement. (C) 2017 Elsevier Inc. All rights reserved.